Organ-coordinated response of early post-germination mahogany seedlings to drought - Horta, Lívia P.; Braga, Márcia R.; Lemos-Filho, José P.; Modolo, Luzia V. (Tree physiology, 2014)
Water deficit tolerance during post-germination stages is critical for seedling recruitment. In this work, we studied the effect of water deficit on morphological and biochemical responses in different organs of newly germinated mahogany (Swietenia macrophylla King) seedlings, a woody species that occurs in the Amazon rainforest. The root : shoot ratio increased under water deficit. The leaf number and water potential were not altered, although reductions in leaf area and stomatal conductance were observed. Osmotic potential became more negative in leaves of seedlings under severe stress. Water deficit increased fructose, glucose, sucrose and myo-inositol levels in leaves. Stems accumulated fructose, glucose and l-proline. Nitric oxide (NO) levels increased in the vascular cylinder of roots under severe stress while superoxide anion levels decreased due to augmented superoxide dismutase activity in this organ. Water deficit induced glutathione reductase activity in both roots and stems. Upon moderate or severe stress, catalase activity decreased in leaves and remained unaffected in the other seedling organs, allowing for an increase of hydrogen peroxide (H2O2) levels in leaves. Overall, the increase of signaling molecules in distinct organs—NO in roots, l-proline in stems and H2O2 and myo-inositol in leaves—contributed to the response of mahogany seedlings to water deficit by triggering biochemical processes that resulted in the attenuation of oxidative stress and the establishment of osmotic adjustment. Therefore, this body of evidence reveals that the development of newly germinated mahogany seedlings may occur in both natural habitats and crop fields even when water availability is greatly limited.